2022
DOI: 10.3934/ctr.2022010
|View full text |Cite
|
Sign up to set email alerts
|

Design of a hybrid high-throughput fused deposition modeling system for circular economy applications

Abstract: <abstract> <p>In recent years, recycling of plastics has opened several doors of advancements in the field of additive manufacturing (AM). The process of fused deposition modelling (FDM) has already been utilized for reprocessing waste plastics into filaments and finally printing them into useful products. Yet another concept of extrusion additive manufacturing (EAM) is gaining lots of attention. In this work, a screw assisted system based on EAM is designed and installed alongside a pre-existing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The reason for this large nozzle size is that this printer was designed as a hybrid system where recycled material will be used as pellets for the infill through direct deposition and for better finishing of the filament system on the visible faces of the part (outer walls, and top and bottom layers). In order to guarantee a high throughput and slicing compatibility between both deposition systems, a nozzle size of a similar diameter to the pellet nozzle was used; more information can be found in [ 41 ].…”
Section: Cyber Physical Production System and Design Of Experimentsmentioning
confidence: 99%
“…The reason for this large nozzle size is that this printer was designed as a hybrid system where recycled material will be used as pellets for the infill through direct deposition and for better finishing of the filament system on the visible faces of the part (outer walls, and top and bottom layers). In order to guarantee a high throughput and slicing compatibility between both deposition systems, a nozzle size of a similar diameter to the pellet nozzle was used; more information can be found in [ 41 ].…”
Section: Cyber Physical Production System and Design Of Experimentsmentioning
confidence: 99%
“…As shown in Supplemental Table 14, researcher established the relationships between screw rotation and the various types of flow rate in the extruder based on different theories. [122][123][124][125] Data obtained during tool path generation is then converted to G and M codes as shown in Supplemental Figure 34(a). This G and M codes have been used along with 3-axis CNC milling machines (Okuma, Japan) for the printing of AM objects.…”
Section: Tool Path Generation For Pellets Extrusion 118mentioning
confidence: 99%
“…Fused deposited modelling (FDM) appears to be a promising technology to employ in 2023, as research in this area has advanced since open-source printers became available on the market. Previous studies have indicated that having successfully printed composites may bring about industrial advantages due to their ability to broaden the economic impact whilst increasing the recyclability of polymeric composite materials [1]. Achieving a proper understanding and functional capability of polymeric composite samples or products through FDM printing will allow greater versatility, especially in metal-composite materials [2].…”
Section: Introductionmentioning
confidence: 99%